2008
DOI: 10.1118/1.2962607
|View full text |Cite
|
Sign up to set email alerts
|

TU‐EE‐A1‐03: Multileaf Collimator Performance and Quality Assurance For Volume Modulated Arc Therapy

Abstract: Purpose: The purpose of this study was to determine the effects of Multi Leaf Collimator (MLC) leaf velocity on leaf positional accuracy during modulated arc delivery. Method and Materials: MLC performance was measured for intensity modulated arcs delivered on a Varian21EX equipped with a 120‐leaf dynamic MLC. The performance of the MLC was tested using arc‐based delivery sequences developed by the investigators for routine MLC leaf velocity testing. MLC performance was also tested using actual VMAT delivery s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Furthermore, it has been shown that there is a relationship between the leaf speed and the inaccuracy of the leaf positions for arc therapy such that at higher leaf speeds, the magnitude of positional errors increases. ( 14 , 15 )…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that there is a relationship between the leaf speed and the inaccuracy of the leaf positions for arc therapy such that at higher leaf speeds, the magnitude of positional errors increases. ( 14 , 15 )…”
Section: Discussionmentioning
confidence: 99%
“…An additional limitation is that the dose calculation in this study was only performed at fixed gantry samples and not at the intermediate position between the samples, and if the dose calculation were performed for the intermediate positions, then we would observe increased dose to the OAR. This increased dose to the OAR could be avoided by turning the dose rate to zero when the leaves sweep across the OAR; however, this would lead to a plan with large fluctuations in both dose rate and leaf positions which would lead to both delivery inefficiency and possible delivery error (Ramsey et al 2001(Ramsey et al , 2008.…”
Section: Discussionmentioning
confidence: 99%